INNOVATIVE FORMS OF SHAPING ORIENTAL EDUCATION IN PRIMARY GRADES - Rejabboyeva Mukharram Odiljon kizi (Web of Journals Publishing, 2025)
This study explores the innovative forms of shaping Oriental education in primary grades in Uzbekistan. It examines the integration of traditional Eastern values and modern pedagogical methods, assessing their effectiveness through statistical analysis and comparative evaluation. The findings highlight the impact of technology, gamification, and collaborative learning on pupils' engagement and retention rates. The research also identifies key challenges, such as access to technology and teacher training, and provides recommendations for further educational improvements.
Keywords: Oriental education, Uzbekistan primary education, innovative teaching methods, gamification, digital learning, cultural heritage in education, experiential learning, curriculum development, teacher training, bilingual education.